MODIFIED METHOD OF A PATH PLANNING ON A LOCAL MAPS FOR TRANSPORT AND AEROSPACE ROBOTS - Anatolyievich, Titenko Evgeny; Gennadyevich, Emelyanov Sergey; Guryevich, Dobroserdov Oleg; Borisovich, Borzov Dmitry; Nikolaevich, Frolov Sergey; Alexsandrovicn, Lisitsin Leonid; Vladimirovna, Bredikhina Natalia; Yuryevich, Sazonov Sergey (Journal of Applied Engineering Science, 2019)
In this paper we consider the modification of the method of planning the A-star path for transport and aerospace robots. It is necessary to take into account obstacles in the local neighborhood of aerospace robot, but not sufficient for the rational path planning. The essence of the modification is to use additional information about the features of original cell array. This additional information is represented by binary flags. They represent obstacle-free rows and matrix columns. The modification allows you to build paths that include straight sections of free cells. The main feature of this method is the use of bitwise logical operations on cell values.